Environmental Study of a Pulp and Paper Mill in NWFP, Pakistan (Biological Sciences - PJSIR, 2006)
A detailed environmental study of a pulp and paper mill was carried out, which included effluent flow measurements and sample collection from some selected points. Stack gas analysis was carried out on the spot. The quantity of raw materials used and their wastage in the production processes were identified. The data obtained were fed into environmental balance sheets, already developed for the mill, which showed excessive use of water per ton production of paper, as compared to a European paper mill. The biological oxygen demand, chemical oxygen demand, and total soluble solids were above the permissible level of National Environmental Quality Standards specified by the Government of Pakistan. Control measures for preventing raw materials wastage, both at in-plant and end-of-pipe treatment, were recommended, which included water conservation, spill control, recovery of valuable fibre, reduction in chlorinated compounds, waste heat recovery, solid waste recovery and its safe disposal for the in-plant controls, while options for the end-of-pipe treatment were discussed with the factory management.